Integrating Sustainability into Maritime Vocational Education: A Study of Lecturers Balancing Doctoral Studies and Teaching - Boy Laksmana (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This research explores the challenges faced by maritime vocational lecturers who are simultaneously pursuing doctoral studies while teaching. The study examines how these lecturers integrate sustainability principles, such as green shipping and port decarbonization, into their curricula, despite the pressures of their dual roles. A qualitative research design was employed, utilizing in-depth interviews with lecturers at maritime vocational schools. The study found that institutional support, time management, and faculty collaboration were crucial in enabling lecturers to effectively balance their teaching and research duties. The research also highlights the importance of flexibility within institutions to support lecturers in integrating sustainability into their teaching practices. The findings suggest that while balancing dual responsibilities is challenging, it is possible to successfully integrate sustainability into vocational pedagogy with appropriate support systems. This study contributes valuable insights for institutions seeking to enhance the integration of sustainability into maritime education and provides a framework for supporting lecturers in their dual roles. The research emphasizes the need for creating a supportive academic environment that fosters the effective integration of sustainability into vocational training, ultimately preparing students for the sustainable challenges of the maritime industry.